Carrier multiplication in germanium nanocrystals - Saeed, Saba (2018)
Carrier multiplication is demonstrated in a solid-state dispersion of germanium nanocrystals in a silicon-dioxide matrix. This is performed by comparing ultrafast photo-induced absorption transients at different pump photon energies below and above the threshold energy for this process. The average germanium nanocrystal size is approximately 5-6 nm, as inferred from photoluminescence and Raman spectra. A carrier multiplication efficiency of approximately 190% is measured for photo-excitation at 2.8 times the optical bandgap of germanium nanocrystals, deduced from their photoluminescence spectra.